(untitled) (LACCEI, 2024)
In this present article the article is carried out the systematic review in various databases and web portals such as: EBSCO, ProQuest, Science Direct, Scielo and Scopus. The bibliography is made up of 20 publications between 2010 - 2021, organized according to: title, author, year, country, database, method, results, measurement instruments, discussions and conclusions, with their respective references. The results show the great importance and impact of the protection against electromagnetic waves with different materials that recently (2021) is being studied with greater interest by the great power countries. New technologies and properties such as the reflection and absorption of electromagnetic waves, in which within the absorption we find materials that waterproof the entry of electromagnetic waves in the construction, such as: the manufacture of polymeric compounds that makes the magnetic properties lose, compound thermoplastic polyurethane, carbonyl iron dispersant, carbon fibers, nano carbon fibers, etc. And in the property of reflection we find the implementation of metallic materials in which I center my work, such as, for example: metallic steel meshes, aluminum, metallic fabrics, conductive wires and fabrics, transparent wood as a solution to the passage of electromagnetic waves and contributions to the environment. It was concluded that the protection against electromagnetic waves is of great importance for our health and care, implementing materials such as metallic fabrics in the construction at the time of the tilework of homes, buildings, etc.